Pelaksanaan Automatic dan Manual Racking memakai PLC CPM2A dan HMI Omron NB5Q - Marina Artiyasa; Nuniek Destria Arianti; Mia Arma Desima; Radete Yulianto; Tri Setya Aji Kumoro; Rendra Aristanto; M Gilang (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2019)
Automatic and Manual Goods Storage System is a tool that functions to store goods in a rack that can be run automatically and manually. This tool can move objects into a storage rack using conveyors, push motors and elevators. The number of objects entering or exiting can be displayed on the HMI screen. This system uses 2 DC motors to move the outlet and inlet, 1 DC motor as a lifter to move up and down, 1 DC motor as a mobile trolly drive, 1 DC motor as a lifter to the left and right. This inlet system uses 3 limit switches to move the conveyor, 6 limit switches for rack indication, 5 limit switches for lifter indication to the right or left, 2 limit switches for mobile trolly indication, 4 limit switches for lifter indication up or down. Users can control the PLC system via HMI. The results of this tool are PLC programs using CX Programmer and HMI using NB Designer can run well. However, this tool is still not perfect due to some imperfect mechanicals, such as a pallet still rubbing against a pallet that is on the rack when racking or loading